2003
DOI: 10.1007/s00294-003-0425-0
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast RNA-binding proteins

Abstract: Chloroplast gene expression is regulated by nucleus-encoded factors, which mainly act at the posttranscriptional level. Plastid RNA-binding proteins (RBPs) represent good candidates for mediating these functions. The picture emerging from recent analyses is that of a great number of differentially regulated RBPs, which are organized in distinct, spatially separated supramolecular complexes. This reflects the complexity of the regulatory network that underlies the intracellular communication system between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 74 publications
0
56
0
Order By: Relevance
“…It has been estimated that up to 5000 unique nuclear genes encode proteins that are targeted to plastids (Martin and Herrmann,participate in stable or transient interactions with plastidencoded proteins or nucleic acids (Barkan and GoldschmidtClermont, 2000;Nickelsen, 2003). Intertaxonomic variability between such partners could trigger nuclear-organellar incompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that up to 5000 unique nuclear genes encode proteins that are targeted to plastids (Martin and Herrmann,participate in stable or transient interactions with plastidencoded proteins or nucleic acids (Barkan and GoldschmidtClermont, 2000;Nickelsen, 2003). Intertaxonomic variability between such partners could trigger nuclear-organellar incompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…This complexity is reflected by the existence of hundreds of nuclear genes encoding predicted organellar RNA binding proteins, many of which are specific to plants (Aubourg et al, 1999;Fedoroff, 2002;Landsberger et al, 2002;Lorkovic and Barta, 2002;Vermel et al, 2002;Belostotsky, 2003;Nickelsen, 2003;Ostheimer et al, 2003;Lurin et al, 2004;Nakamura et al, 2004). Some organellar RNA binding proteins have been detected through their ability to bind RNA in vitro and others have surfaced through genetic screens, but most are unstudied.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analyses have demonstrated that within these UTRs lie cis-elements, often forming secondary structures, which facilitate the interaction with nucleus-encoded RBPs (Yang et al, 1995;Hirose and Sugiura, 1996;Klaff et al, 1997;Alexander et al, 1998;Zou et al, 2003;Merhige et al, 2005). RBPs display an array of functions, including processing of polycistronic transcription units, RNA maturation and editing, transcript stability and turnover, and the recruitment of additional protein factors involved in the initiation of translation in response to the requirements of the cell (Nickelsen, 2003;Schmitz-Linneweber and Barkan, 2007). In contrast to the high level of conservation found within protein-coding regions and ribosomal RNAs, intergenic and UTRs are highly variable in chloroplast genomes (Daniell et al, 2006;Saski et al, 2007;Timme et al, 2007).…”
mentioning
confidence: 99%